2004
DOI: 10.1097/01.sla.0000133355.48672.22
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lymphangiogenesis and Lymphovascular Invasion in Invasive Breast Cancer

Abstract: Our data provide evidence that the biologic system of lymphangiogenesis constitutes a potential new target for development of anti-breast cancer therapeutic concepts. Our results further suggest that young, premenopausal patients with low differentiated breast tumors and high LMVD and LVI would, in particular, benefit from lymphangiogenesis-associated therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
190
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(235 citation statements)
references
References 33 publications
27
190
1
5
Order By: Relevance
“…41,44 Others, however, maintain that the tumor invades new lymphatics that are formed during lymphangiogenesis within the tumor mass or at the invasive front of the tumor. 37,39 In this study, most foci of D2-40 þ lymph vessel invasion occurred at the invasive front of the tumor, indicating that metastasis could occur via pre-existing lymphatics or via newly formed lymphatics at the invasive front of the tumor.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…41,44 Others, however, maintain that the tumor invades new lymphatics that are formed during lymphangiogenesis within the tumor mass or at the invasive front of the tumor. 37,39 In this study, most foci of D2-40 þ lymph vessel invasion occurred at the invasive front of the tumor, indicating that metastasis could occur via pre-existing lymphatics or via newly formed lymphatics at the invasive front of the tumor.…”
Section: Discussionmentioning
confidence: 62%
“…Several studies have demonstrated the absence of lymphangiogenesis in breast cancer whereas others have reported the presence of lymphangiogenesis in breast cancer. [38][39][40][41][42][43][44] Intratumoral lymphangiogenesis, however, has been demonstrated using LYVE-1 in some other cancers such as head and neck squamous cell carcinomas. 45 The current study showed that few if any lymphatics were present within the tumor mass whereas lymphatics were present at the invasive front of the tumor as has been reported in some studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered as a detrimental factor in cancer because metastatic dissemination and early lymph node metastasis are associated with a poor prognosis (Morice et al, 2003;Schoppmann et al, 2004). In contrast, the relevance of neolymphangiogenesis in diseases such as asthma or inflammatory arthritis (Zhang et al, 2007) remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphovascular invasion in tissue sections of tumours has been clearly documented to be a reliable prognostic variable predicting nodal metastasis and survival in breast, cervix cancer and impacts on decision making for therapy in testicular cancer (Warde et al, 1997;Morice et al, 2003;Schoppmann et al, 2004;Dinshaw et al, 2005). However, the prognostic significance of LVD in cancer is not clearcut.…”
Section: Discussionmentioning
confidence: 99%